Industry, vocabulary in the field of economy and its analysis (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article describes the importance of learning foreign languages in our country, the necessity of knowing foreign languages in economic relations, how economic neologisms are used.